Excel Timesaving Techniques for Dummies - Harvey, Greg (Wiley Publishing, 2011)
Covering formulas, charts, data lists, macros, and versions 2000, 2002, and 2003, this book offers more than seventy easy-to-follow techniques that show both new and experienced Excel users how to save time and avoid tedious or redundant tasks. Bestselling author Greg Harvey includes information on customizing Excel's menus and toolbars; modifying Excel's editing settings; using add-ins, AutoCorrect, AutoFill, AutoFormat, and data validation; copying and moving data between worksheets; encrypting workbook files; creating external database queries; converting worksheet data and charts into Web pages; and much more. * Written by Greg Harvey, one of the bestselling technology authors of all time, whose books have combined sales of more than four million copies * A unique, two-column format makes it easy for readers to grasp and apply each technique-and begin working more efficiently